The Association Between Maternal Age and the Incidence of Preeclampsia in the Working Area of Penana’e Community Health Center in 2026 - Yati Purnama; Sri Astuti; Ainun Korimah (Jurnal EduHealth, 2026)
Preeclampsia is one of the leading causes of maternal morbidity and mortality, characterized by elevated blood pressure after 20 weeks of gestation and may be accompanied by proteinuria and other organ dysfunctions. Maternal age is one of the risk factors associated with the occurrence of preeclampsia. This study aimed to determine the relationship between maternal age and the incidence of preeclampsia in the working area of Penana’e Public Health Center, Bima City, in 2025. This research employed an observational analytic method with a case-control design. The study population consisted of 273 pregnant women registered in the working area of Penana’e Public Health Center from January to June 2025. A total of 73 respondents were selected as samples, comprising case and control groups. Data were obtained from medical records and the e-Cohort database of Penana’e Public Health Center. The independent variable was maternal age, while the dependent variable was the incidence of preeclampsia. Data were analyzed using univariate and bivariate analyses through the Chi-Square test and Odds Ratio (OR) calculation. The results showed that most respondents were aged 20–35 years (44 respondents; 60.3%), while 13 respondents (17.8%) were aged below 20 years and 16 respondents (21.9%) were aged above 35 years. The case group (preeclampsia) consisted of 32 respondents (43.8%), whereas the control group (non-preeclampsia) consisted of 41 respondents (56.2%). The Chi-Square test indicated a significant relationship between maternal age and the incidence of preeclampsia (p = 0.005). Odds Ratio analysis revealed that pregnant women aged below 20 years had a 4.27 times greater risk of developing preeclampsia compared to those aged 20–35 years, while pregnant women aged above 35 years had an 8 times greater risk. It can be concluded that there is a significant relationship between maternal age and the incidence of preeclampsia. Therefore, healthcare providers are expected to strengthen screening, education, and pregnancy monitoring among women in high-risk age groups to prevent preeclampsia and reduce maternal morbidity and mortality.